University, popular movements and Dialogue of Knowledge (Praxis Educativa, 2023)
I present here the topic of the Dialogue of Knowledge as the structuring of a political alliance between the university world and the popular movements. It begins with a brief memory of some elements that have been present throughout the Latin American-Caribbean regional history in this effort that is not new, but has had important contributions between the end of the 20th century and so far in the 21st. I analyze the characteristics and components of this Dialogue of Knowledge from the principles of interculturality from the unity of the political and the epistemic and from the proposal to start from the option for a specific epistemic-political place: the praxis of popular struggles for the life. Finally, I highlight the importance of deepening this path for the strengthening of popular organizations and struggles and for the realization of a popular and decolonizing path for our universities.
Keywords: Knowledge Dialogue; university and popular movements; interculturality; epistemic-political place; praxis of popular struggles for life